A escola e o bairro entre o público e o privado: um estudo da concepção do Programa de Gestão Comunitária da Associação Cidade Escola Aprendiz - Freitas, Mayara de (2013)
This study has enquired the Bairro-Escola conception, a social program from the ONG Associação Cidade Escola Aprendiz. Terms such as Bairro-Escola , Educador Comunitário , and Gestor Público em Educação Comunitária have had their meanings analyzed according to community, partnership, and social justice ideas. The data on Bairro-Escola were collected from its documentation in websites, manuals, projects, etc. From this data, the Bairro-Escola s purposes have been compared to the theoretical concepts which one alleges to guide this program. One seeks to know how the Associação Cidade Escola Aprendiz s policy is conducted by compensatory actions which are part of modernization, rationalization, and result management projects that they have been developed in the brazilian education policy. That research has in Max Weber, John Rawls, Maurício Tragtenberg, and Evelina Dagnino s studies their theoretical support. In those studies, concepts as work, progress, modernization, rationalization (Weber), fairness, social justice (Rawls), management, self-management, ideology, administration (Tragtenberg), perverse confluence, participation, and citizenship (Dagnino) are discussed. In this study, we found some concepts about education within the Bairro-Escola project from the Associação Cidade Escola Aprendiz. Communitarian education features are like the perverse confluence, that look for improving the human and social capital by development of their abilities. This development has a constitutive ambiguity between the mercantile interests in maximizing profits and the public image based on "social responsibility."